(untitled) (diségno, 2023)
From 12 to 15 June 2023, the castello del Valentino, an UNESCO World Heritage Site and the elegant venue of the Department of Architecture and Design (DAD) of the Politecnico di Torino, together with the prestigious independent publisher of books on architecture and mathematics Kim Williams books, hosted the fourteenth edition of the international and interdisciplinary conference entitled Nexus 2023: Relationships Between Architecture and Mathematics. After the Covid-19 pandemic, which in 2020 precluded the conference from being held in presence in Kaiserlautern (Germany), 2023 represented a return to normality by allowing scholars and young researchers to meet again in presence and engage in exchanges that could fuel scientific debate and stimulate new ideas and collaborations for future research. [read more]